PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA APOTEK K-24 SURABAYA - Sholeh Ibrahim; Jimmy Ignatius (Bisnis-Net, 2023)
The spread of covid-19 in indonesia had had a very extraordinary impact on all indonesian people.  The non-essential sector had experienced an extraordinary impact, many non-essential companies had had to closed their businesses due to government policies that implement worked from home policies to limit interactions that caused the spread of covid-19.  This studied aims to determine the effect of service quality and brand image on purchasing decisions of k-24 pharmacy Surabaya.  The typed of researched used in this researched was quantitative.  In particular, sampling techniques were often used to collected random data with researched data analysis instruments that had the quantitative statistical aimed of testing hypotheses.  The influence of service quality variables on purchasing decisions had a t valued of 2.706 and a significant valued of 0.009.  This means that the service quality variable had a significant influence on the purchasing decision variable.  The influence of the brand image variable on purchasing decisions had a t valued of 3.847 and a calculated valued of 0.000.  This means that the brand image variable had a significant influence on the purchasing decision variable.  Based on the results of the studied, it shows that the service quality variable had a significant influence on the purchasing decision variable.  Then the brand image variable had a significant influence on the purchasing decision variable.  Based on the researched results above, the author concludes that the service quality variable (x1) and the brand image variable (x2) had a simultaneous effect on the purchasing decision variable (y)